Fucose as a potential therapeutic molecule against the immune-mediated inflammation in IgA nepharopathy: An unrevealed link - Qing, Jianbo; Hu, Xueli; Li, Changqun; Song, Wenzhu; Tirichen, Hasna; Yaigoub, Hasnaa; Li, Yafeng (Frontiers in Immunology, 2022)
Background IgA nephropathy (IgAN) is an autoimmune disease that affects people of any age and is an important cause of end-stage renal disease. However, the pathogenesis and pathophysiology of IgAN is not clear. This article aimed to explore the immune-mediated inflammation and genetic mechanisms in IgAN. Methods The transcriptome sequencing data of IgAN glomeruli in the Gene Expression Omnibus (GEO) database were downloaded. Single Sample Gene Set Enrichment Analysis (ssGSEA) was used to estimate the immune microenvironment of the merged microarray data and GSE141295. IgAN samples were divided into two clusters by cluster analysis. “limma” and “DEseq2” package in R were used to identify differentially expressed genes (DEGs). The Weighted Gene Co-Expression Network Analysis (WGCNA) was used to identify the co-expression modules related to inflammation in IgAN. R software package “clusterProfiler” was used for enrichment analysis, while Short Time-Series Expression Miner (STEM) Analysis was used to identify the trend of gene expression. Machine-learn (ML) was performed using the shiny app. Finally, Drug Signatures database (DSigDB) was used to identify potential molecules for treating IgAN. Results The infiltration of macrophages in IgAN glomeruli was increased, while CD+T cells, especially inducedregulatory T-cells(iTregs) were decreased. 1104 common DEGs were identified from the merged data and GSE141295. Brown module was identified to have the highest inflammatory correlation with IgAN using WGCNA, and 15 hub genes were screened from this module. Among these 15 hub genes, 14 increased with the severity of IgAN inflammation based on STEM analysis. Neural network (nnet) is considered as the best model to predict the severity of IgAN. Fucose identified from DSigDB has a potential biological activity to treat IgAN. Conclusion The increase of macrophages and decrease of iTregs are immune signatures of IgAN glomeruli. In this study, 15 hub genes associated with severe inflammation were identified. Among them, 14 hub genes were used to construct a nnet model to predict and evaluate the inflammation of IgAN. A molecule called fucose that may become an effective drug for IgAN in the future was predicted.